2018
DOI: 10.1161/circinterventions.117.006023
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Flow Ratio Identifies Nonculprit Coronary Lesions Requiring Revascularization in Patients With ST-Segment–Elevation Myocardial Infarction and Multivessel Disease

Abstract: In a limited and selected study population, our study showed that QFR computation may be a safe and reliable tool to guide coronary revascularization of NCLs in ST-segment-elevation myocardial infarction patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
108
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 90 publications
(117 citation statements)
references
References 19 publications
7
108
0
2
Order By: Relevance
“…We found a high classification agreement between acute QFR and staged QFR with no relation to follow‐up time. These results are in line with a proof of concept study that indicated that QFR assessment of NCLs was not notably affected by nonculprit physiological alterations induced by STEMI . In contrast, the main iSTEMI study showed that the agreement of acute iFR with staged iFR was lower and with increasing difference with increasing time interval between acute and staged iFR assessment .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We found a high classification agreement between acute QFR and staged QFR with no relation to follow‐up time. These results are in line with a proof of concept study that indicated that QFR assessment of NCLs was not notably affected by nonculprit physiological alterations induced by STEMI . In contrast, the main iSTEMI study showed that the agreement of acute iFR with staged iFR was lower and with increasing difference with increasing time interval between acute and staged iFR assessment .…”
Section: Discussionsupporting
confidence: 87%
“…These results are in line with a proof of concept study that indicated that QFR assessment of NCLs was not notably affected by nonculprit physiological alterations induced by STEMI. 11 In contrast, the main iSTEMI study showed that the agreement of acute iFR with staged iFR was lower and with increasing difference with increasing time interval between acute and staged iFR assessment. 4 While QFR was slightly higher in the acute setting, iFR was significantly lower.…”
Section: Discussionmentioning
confidence: 87%
“…The diagnostic precision of QFR in nonculprit lesions, as recently assessed in a proof concept study by Spitaleri et al, could thus not be confirmed 26. We excluded lesions with Medina type 1.1.1 and 1.0.1 bifurcations attributed to specific limitations of the present QFR application; hence, the diagnostic precision of QFR in bifurcation needs further developments and investigation.…”
Section: Study Limitationsmentioning
confidence: 77%
“…The calculation of the cQFR incorporates the frame counting at rest to compute mean HFV as a boundary condition . A recent study indicated that both fQFR and cQFR directly correlated with FFR, and that cQFR was relatively higher than fQFR in the myocardial infarction‐related coronary arteries, while no such difference was found in noninfarction cases . These interesting results suggested that cQFR which incorporates HFV might be strongly influenced by MVD.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Recently, a novel approach has been developed, enabling rapid computation of FFR pullbacks from three-dimensional (3D) quantitative coronary angiography. [17][18][19][20] The computational FFR, also termed quantitative flow ratio (QFR), can be obtained using two different flow models: fixed-flow QFR (fQFR) using empiric hyperemic flow velocity (HFV) and contrast-flow QFR (cQFR) using HFV derived from coronary angiography. 21,22 Because fQFR is based only on anatomic information obtained from 3D-QCA, it does not reflect the influence of microcirculation function.…”
mentioning
confidence: 99%